CURRENT FERTILITY PRESERVATION METHODS IN WOMEN WITH CANCER - E. A. Fazlyeva; M. P. Mironova; G. G. Faskhutdinova; D. V. Islamgulov (Креативная хирургия и онкология)
Advances  in the diagnosis and  treatment of cancer  have greatly enhanced the life expectancy of women with cancer.  As a result, there is a growing population of adolescent and  adult long-term survivors of cancer.  The continuous development of techniques of assisted human reproduction has  led to important strategies in an  attempt to maintain reproductive function in patients subjected to chemoand  radiotherapy treatment of cancer, among them cryopreservation of embryos, gametes, and  ovarian cortical tissue.